Strain-Insensitive Hierarchically Structured Stretchable Microstrip Antennas for Robust Wireless Communication - Zhu, Jia; Zhang, Senhao; Yi, Ning; Song, Chaoyun; Qiu, Donghai; Hu, Zhihui; Li, Bowen; Xing, Chenghao; Yang, Hongbo; Wang, Qing; Cheng, Huanyu (Nano-Micro Letters, 2021)
As the key component of wireless data transmission and powering, stretchable antennas play an indispensable role in flexible/stretchable electronics. However, they often suffer from frequency detuning upon mechanical deformations; thus, their applications are limited to wireless sensing with wireless transmission capabilities remaining elusive. Here, a hierarchically structured stretchable microstrip antenna with meshed patterns arranged in an arched shape showcases tunable resonance frequency upon deformations with improved overall stretchability. The almost unchanged resonance frequency during deformations enables robust on-body wireless communication and RF energy harvesting, whereas the rapid changing resonance frequency with deformations allows for wireless sensing. The proposed stretchable microstrip antenna was demonstrated to communicate wirelessly with a transmitter (input power of − 3 dBm) efficiently (i.e., the receiving power higher than − 100 dBm over a distance of 100 m) on human bodies even upon 25% stretching. The flexibility in structural engineering combined with the coupled mechanical–electromagnetic simulations, provides a versatile engineering toolkit to design stretchable microstrip antennas and other potential wireless devices for stretchable electronics. Highlights: 1 The “ordered-unraveling” of hierarchical structures from mechanical assembly contributes to not only the improved overall stretchability, but also the small resonance shift of the stretchable microstrip antenna upon stretching. 2 The mechanical-electromagnetic properties of stretchable microstrip antennas can be controlled by changing the number of arches in the meshed patch. 3 A double-arched microstrip antenna was demonstrated to communicate wirelessly upon 25% stretching or when being placed on human bodies.